Feasibility Study on Long-Lived Fission Products Transmutation in Equilibrium Fuel Cycles of PWR - Abdul Waris; H. Sekimoto (Institut Teknologi Bandung, 2005)
A study on long-lived fission products (LLFP) transmutation in equilibrium fuel cycles of pressurized water reactors (PWR) has been performed. The seven important LLFP, i.e., 79Se, 93Zr, 99Tc, 107Pd, 126Sn, 129I, and 135 Cs were considered in this study. In order to get a comprehensive perspective, single isotope/element transmutations and mixed isotopes/elements transmutations for both isotopic separation and elemental separation were employed. The calculation results showed that the transmutation of the all seven LLFP together with isotopic separation are feasible by increasing the required enrichment of loaded uranium fuel up to 7.1wt% for standard PWR. Isotopic separation is not necessary for mixed technetium and iodine transmutation. The transmutation of the all seven LLFP together with elemental separation may not possible since zirconium transmutation in PWR is a formidable task.